2017
DOI: 10.3324/haematol.2016.156844
|View full text |Cite
|
Sign up to set email alerts
|

Acute myeloid leukemias with ring sideroblasts show a unique molecular signature straddling secondary acute myeloid leukemia and de novo acute myeloid leukemia

Abstract: Acute myeloid leukemias with ring sideroblasts show a unique molecular signature straddling secondary acute myeloid leukemia and de novo acute myeloid leukemia Ring sideroblasts (RS) are a distinct morphological feature present in myelodysplastic syndromes (MDS), myelodysplastic/myeloproliferative neoplasms (MDS/MPN) and acute myeloid leukemia (AML). The International Working Group on Morphology of Myelodysplastic Syndrome (IWGM-MDS) defines them as erythroblasts with a minimum of 5 siderotic granules covering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
5
1
Order By: Relevance
“…Although RS are generally regarded as a specific feature of certain MDS subtypes, the reported incidence of 25% indicates that RS is -log10 -value p also a rather common finding in AML. 18 In contrast to reports on MDS-RS subtypes, mutations in spliceosome gene SF3B1 were rarely observed in our RS-AML cohort. The paucity of this mutation in RS-AML might be explained by the low tendency toward AML transformation from MDS subtypes with SF3B1 mutations.…”
Section: Discussioncontrasting
confidence: 92%
See 3 more Smart Citations
“…Although RS are generally regarded as a specific feature of certain MDS subtypes, the reported incidence of 25% indicates that RS is -log10 -value p also a rather common finding in AML. 18 In contrast to reports on MDS-RS subtypes, mutations in spliceosome gene SF3B1 were rarely observed in our RS-AML cohort. The paucity of this mutation in RS-AML might be explained by the low tendency toward AML transformation from MDS subtypes with SF3B1 mutations.…”
Section: Discussioncontrasting
confidence: 92%
“…These results are in agreement with a previous study using a restricted gene panel to analyze the RS phenotype in patients with AML. 18 The high incidence of poor-risk cytogenetic aberrancies, including chromothripsis, probably reflects the high frequency of TP53 mutations. 30 In the present study, we have primarily included patients with de novo AML reflecting the lack of a clinical relevant history of antecedent MDS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We had a single case of a male patient diagnosed at a relatively younger age (37 years old) and considered the youngest among all groups of myeloid neoplasms with RS in our cohort. Martin-Cabrera et al 13 recently reported that AML with RS shows a unique molecular signature straddling secondary AML and de novo AML.…”
Section: Comparison Between Acquired Clonal (Neoplastic) Cases and No...mentioning
confidence: 99%